Identifying Novel Targets to Restore Defects in Neurogenesis in the 3xTG Mouse Model of Alzheimer's Disease - Abdi, Amaal Abdullahi (Université d'Ottawa / University of Ottawa, 2022)
Alzheimer's disease (AD), marked by a serious and progressive decline in cognitive abilities, is a severely debilitating disease that is becoming an increasing concern with our aging population. Defects in neurogenesis have been shown to exist in AD and aggravate the neuropathology and cognitive deficits associated with the disease. In this study, I aimed to characterize the cellular and molecular defects of neurogenesis in the triple transgenic mouse model of AD (3xTG). To do so, I first performed a detailed immunohistochemistry characterization using neurogenic markers that were quantified and analyzed in the hippocampus of control and 3xTG mice. This analysis not only revealed an overall decrease in the pool of neural stem and progenitor cells (NSPCs) in 3xTG brains, but also defects in proliferation, differentiation and a loss within the neuroblast, immature neuron and mature neuron populations. Subsequent immunohistochemistry analysis of two molecular targets, Hopx and LPAR1, involved in NSC maintenance and proliferation respectively, revealed their dysregulation in 3xTG brains, providing some indication of molecular defects underlying this loss. The neurosphere assay was next employed to assess cell-autonomous defects and fewer neurospheres were formed from cultured 3xTG NSPCs, suggesting a defect in NSPC pool expansion that is intrinsic to 3xTG NSPC function. Molecular characterization of these cultured NSPCs via qPCR revealed the upregulation of mitochondrial and fatty acid oxidation genes in 3xTG NSPCs, suggesting not only a dysregulation of metabolic functions, but also an acclimation to oxidative stress conditions. Interestingly, 3xTG NSPCs formed larger and more neurospheres when grown in galactose medium - which is used to simulate oxidative stress - relative to the control, confirming an adaptative response to oxidative stress conditions. Further characterization of these cellular defects and underlying molecular mechanisms can reveal novel therapeutic strategies for AD.
Keywords: neurogenesis; Alzheimer's Disease; neural stem cells; 3xTG-AD